Characterization of the Spanish Pomegranate Germplasm Collection Maintained at the Agricultural Experiment Station of Elche to Identify Promising Breeding Materials - Zuriaga, Elena; Pintová, Jitka; Bartual, Julián; Badenes, María L. (MDPI, 2022)
Pomegranates were one of the first domesticated fruit crops, and their long history resulted in the development of local cultivars all over the world. Spain is one of the main producers and exporters of this crop in the Mediterranean Basin, but in order to maintain the competitiveness of this crop, new varieties should be developed. For this purpose, the pomegranate germplasm collection hold at the Agricultural Experiment Station of Elche, a public institution dependent on the Valencian regional government, is an interesting tool. However, the detailed characterization of any germplasm collection is a fundamental requirement to be able to make the most of these resources, allowing to identify putative promising accessions and to optimize the design of the future crosses. In this work, the genetic diversity of 94 accessions of this collection was analyzed using 19 microsatellite markers. As a result, 85 different genotypes were identified. These genetic profiles could be useful for varietal identification. Despite this genetic diversity, no clear substructure was observed, except for the ornamental accessions, that could be related to the vegetative propagation of the species. Additionally, the morphological characterization of this collection has made it possible to identify some materials that may be of interest as a source of traits for breeding. Results presented here pave the way for further genetic analyses, allowing the selection of parents to obtain segregating populations, as well as their descendants by the use of molecular assisted selection.